Evaluation of the Relationship Between Self-Care and Treatment Compliance in Patients with Type 2 Diabetes: A Cross-Sectional Study from Northeast Türkiye - Caner, Enver; Kavuran, Esin (Makara Journal of Health Research, 2024)
Background: The study aimed to investigate the connection between self-care behaviors and treatment adherence among individuals with type 2 diabetes. Methods: This cross-sectional correlational study was conducted between January and May 2022 in a public hospital involving 191 patients diagnosed with type 2 diabetes. Data were collected using the patient information form, the diabetes self-care scale, and the assessment scale for treatment compliance in type 2 diabetes. Results: The mean self-care score was 84.57 ± 14.46 years, and the mean treatment compliance score was 79.50 ± 11.13 years, with a significant negative correlation between them (r = −0.315, p < 0.001). Factors positively influencing self-care were being female (p < 0.05), unemployed (p < 0.05), farmer or civil servant (p < 0.05), hospitalized in the past year (p < 0.01), and exercising regularly or occasionally (p < 0.001). Treatment compliance was significantly higher in those who did not exercise (p < 0.01). A positive correlation was found between age and treatment compliance (r = 0.152, p < 0.05) but not with BMI or diagnosis duration. Conclusions: The study revealed that patients exhibited moderate levels of self-care and treatment compliance. Moreover, as self-care improved, treatment compliance tended to decrease.